Pathogenesis of ANCA-Associated Pulmonary Vasculitis - Alba, Marco A.; Jennette, J. Charles; Falk, Ronald J. (Seminars in Respiratory and Critical Care Medicine, 2018)
Antineutrophil cytoplasmic antibodies (ANCAs) are autoantibodies specific for antigens located in the cytoplasmic granules of neutrophils and lysosomes of monocytes. ANCAs are associated with a spectrum of necrotizing vasculitis that includes granulomatosis with polyangiitis, microscopic polyangiitis, and eosinophilic granulomatosis with polyangiitis. Pulmonary vasculitis and related extravascular inflammation and fibrosis are frequent components of ANCA vasculitis. In this review, we detail the factors that have been associated with the origin of the ANCA autoimmune response and summarize the most relevant clinical observations, in vitro evidence, and animal studies strongly indicating the pathogenic potential of ANCA. In addition, we describe the putative sequence of pathogenic mechanisms driven by ANCA-induced activation of neutrophils that result in small vessel necrotizing vasculitis and extravascular granulomatous necrotizing inflammation.
Keywords: ANCA; granulomatosis with polyangiitis; microscopic polyangiitis; pulmonary vasculitis